Crystal structure, PIXEL calculations of intermolecular interaction energies and solid-state characterization of the herbicide isoxaflutole - Jascha Schinke; Thomas Gelbrich; Ulrich J. Griesser (Acta Crystallographica Section E: Crystallographic Communications, 2022)
In the isoxaflutole molecule {systematic name: (5-cyclopropyl-1,2-oxazol-4-yl)[2-(methylsulfonyl)-4-(trifluoromethyl)phenyl]methanone; C15H12F3NO4S}, the 1,2-oxazole and methanone fragments form an almost coplanar unit, whereas the methanone and phenyl mean planes are inclined by an angle of more than 60°. This conformation differs fundamentally from all other known examples of the 1,2-oxazol-4-yl(phenyl)methanone fragment and is ascribed to the presence of the bulky methylsulfonyl para substituent at the phenyl ring. PIXEL calculations reveal that the largest contributions to the stabilization of the crystal persist within a columnar arrangement of molecules along the twofold screw axis and in interactions between adjacent columns related by an inversion operation. Both these intra-column and inter-column motifs are dominated by the dispersion energy term but also display additional significant stabilization effects as a result of three short intermolecular C—H...O contacts involving the methanesulfonyl-O atoms.